KEY TRENDS IN THE DEVELOPMENT OF LAND TRANSPORT INFRASTRUCTURE IN RUSSIA’S ARCTIC REGIONS DURING THE PRE-PANDEMIC PERIOD - Natalia A. Serova; Valentina A. Serova (Север и рынок: формирование экономического порядка)
The implementation of national projects for establishing a unified national transport network determines the relevance of studying the spatial organization of transport infrastructure, including the assessment of transport development across individual regions. One such region is the Arctic zone of the Russian Federation, a macro-region with unique characteristics. This study aims to identify interregional differences in the development of land transport infrastructure in Russia’s Arctic regions and assess the adequacy of transport provisions in meeting current and potential cargo transportation demands during the pre-pandemic period. The authors conducted a retrospective analysis of changes in the length of paved public roads and the operational railway network in the Arctic regions, focusing on the period from 2000 to 2020. Key indicators of transport security, such as the Engel, Uspensky, and Vasilevsky coefficients, were used for nonlinear evaluation. The scientific novelty of this research lies in uncovering key trends and patterns in land transport infrastructure development and assessing the level of transport security in the Russian Arctic during the pre-pandemic era. The study’s findings confirm persistent territorial imbalances in land transport infrastructure development and interregional disparities in the pace and scale of new road and railway construction. The main insights and conclusions of this article can inform public authorities when preparing territorial strategies and transport infrastructure development programs for the Arctic regions, as well as in the training of state and municipal officials. The authors’ future research will focus on exploring trends and specificities of land transport development under current geopolitical conditions, aiming to evaluate the effectiveness of public policy in developing a backbone transport network in the Arctic during times of crisis.